Pengembangan Materi Ajar Berbasis Ekowisata Mangrove dalam Pembelajaran IPA: Review - Hariani, Riri (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2024)
Science learning in schools often emphasizes rote memorization of content, rather than applying knowledge in real-life contexts. The objective of this research is to explore the development of teaching materials based on mangrove ecotourism and their effectiveness in science education. The method employed in this study is literature review. Articles were reviewed through a national-level literature search using selected sources (databases), namely Google Scholar. The search terms included "mangrove ecotourism," "ecosystem," "science," and "teaching materials”. Ten articles published in national or international journals within the last 10 years were utilized. The research findings indicate that mangrove ecotourism materials can be effectively used in junior high school science education. Through interactive and field-based activities, students can grasp ecological concepts, biodiversity, conservation, and sustainability. Integrating mangrove ecotourism into the science curriculum not only enriches learning experiences but also enhances students' awareness and concern for the environment.